Capacitación en mecánica automotriz a los estudiantes de la Unidad Educativa Manuela Cañizares para el conocimiento del sistema de inyección electrónica de los vehículos a gasolina - Paredes Lara, Teodoro Viterbo (2021)
This research project was carried out at the Manuela Cañizares Educational Unit with the sole purpose of training students in mechanics, emphasizing the preventive maintenance of the electronic injection system in gasoline vehicles, making them aware of its importance, advantages and displaying techniques , values both social and in the labor field in students, obtaining the expected results, demanding a greater commitment with teachers to renew their knowledge through improved techniques and methodologies that attract interest or motivate students to learn more about automotive mechanics, since fuel injection makes it possible to have an excellent distribution in terms of the intake system, to achieve an increase in power in multi-cylinder car engines, due to the improvement involved in the intake systems. This makes fuel injection systems advantageous for car engines. Due to the deficiency of the institution in which this study was conducted, the teaching and learning process provided to the students is flawed. Teachers they need further updates on the use of technical tools to detect injection system damage quickly and efficiently and to be able to perform proper maintenance on various vehicles.